Addiction as a defence against relationship? Relationship as an antidote to addiction? A phenomenological exploration of the significance of relationship in recovery - Hewitt Evans, Joanna; Ryan, Andy (European Journal for Qualitative Research in Psychotherapy, 2012)
This paper is a joint project, undertaken by Andy, an Integrative psychotherapist and recovered alcoholic and Joanna, a Ge- stalt psychotherapist, supervisor and trainer. Working together as co-researchers, we tell Andy’s story. Some of the details contained in the story are shocking but we believe that sharing them offers the reader the opportunity to enter more fully into Andy’s experience and adds a further dimension to the relational model of this research. Our relationship began as trainee psychotherapist and supervisor and has developed over several years to one of peers and friends. Andy has, alongside training as a psychotherapist, developed his thinking substantially in the field of addiction, worked innovatively and creatively within a residential treatment centre and become a leader in various forums relating to addiction. He has recently begun to offer training in this area to other workers in the field, including psychotherapists and brims with enthusiasm when sharing his ideas and experience. Along the way Joanna became involved as a workplace supervisor for Andy and colleagues and her interest in addiction, supported by personal family history, a much loved grand- father who died of alcoholism, grew. We both believe that relationship is the key to healing and that developing relational approaches in the field of alcoholism and addiction is the way forward. In terms of funding and discussion there is currently a move to make abstinence a goal rather than substance substitution, yet abstinence itself does not necessarily prevent dysfunction in other areas. By combining our skills and experience we aim to explore what is significant in terms of rela- tionship, addiction and recovery.